Bacterial colonisation in patients with bronchiectasis: microbiological pattern and risk factors. Issue 1 (1st January 2002) - Angrill, J; Agustí, C; de Celis, R; Rañó, A; Gonzalez, J; Solé, T; Xaubet, A; Rodriguez-Roisin, R; Torres, A
Abstract : Background: A study was undertaken to investigate the incidence, diagnostic yield of non-invasive and bronchoscopic techniques, and risk factors of airway colonisation in patients with bronchiectasis in a stable clinical situation. Methods: A 2 year prospective study of 77 patients with bronchiectasis in a stable clinical condition was performed in an 800 bed tertiary university hospital. The interventions used were pharyngeal swabs, sputum cultures and quantitative protected specimen brush (PSB) bacterial cultures (cut off point ≥10 2 cfu/ml) and bronchoalveolar lavage (BAL) (cut off point ≥10 3 cfu/ml). Results: The incidence of bronchial colonisation with potential pathogenic microorganisms (PPMs) was 64%. The most frequent PPMs isolated were Haemophilus influenzae (55%) and Pseudomonas spp (26%). Resistance to antibiotics was found in 30% of the isolated pathogens. When the sample was appropriate, the operative characteristics of the sputum cultures were similar to those obtained with the PSB taken as a gold standard. Risk factors associated with bronchial colonisation by PPMs in the multivariate analysis were: (1) diagnosis of bronchiectasis before the age of 14 years (odds ratio (OR)=3.92, 95% CI 1.29 to 11.95), (2) forced expiratory volume in 1 second (FEV1 ) <80% predicted (OR=3.91, 95% CI 1.30 to 11.78), and (3) presence of varicose or cystic bronchiectasis (OR=4.80, 95% CI 1.11 to 21.46). Conclusions: Clinically stable patients with bronchiectasis have a high prevalence of bronchial colonisation by PPMs. Sputum culture is a good alternative to bronchoscopic procedures for evaluation of this colonisation. Early diagnosis of bronchiectasis, presence of varicose-cystic bronchiectasis, and FEV1 <80% predicted appear to be risk factors for bronchial colonisation with PPMs.